Stability of densities for perturbed diffusions and Markov chains - Konakov, Valentin; Kozhina, Anna; Menozzi, Stéphane (Probability and statistics, 2017)
We study the sensitivity of the densities of non degenerate diffusion processes and related Markov Chains with respect to a perturbation of the coefficients. Natural applications of these results appear in models with misspecified coefficients or for the investigation of the weak error of the Euler scheme with irregular coefficients.